From Classroom Explanation to Public Engagement: A Systematic Review of Science Communication Practices in Formal Education - Lianto; Robi'atul Adawiyah, Marosa; Ayu Lestari, Tri; Amaliya Rha'ifa, Febrina; Rahmawati, Salsabila (LITPAM, 2026)
Science communication is increasingly recognized as a key competency in science education; however, its implementation within formal educational settings remains fragmented. Using a systematic literature review approach based on the Denyer and Tranfield framework and guided by the PRISMA protocol, this study synthesized 13 empirical studies published between 2016 and 2025 to examine how science communication is integrated into formal science education and to develop a developmental framework that explains its progression across educational levels. The findings indicate that science communication is predominantly embedded within active-learning pedagogies, including inquiry-based, problem-based, and project-based learning. In school contexts, communication practices are largely limited to classroom-bound activities such as explaining experimental results and reporting findings. In contrast, undergraduate education demonstrates a broader range of practices, including podcast production, blog writing, Wikipedia editing, and press release development, often targeting non-expert audiences. The review highlights three key patterns. First, science communication is most effectively developed when integrated into authentic learning tasks. Second, communication practices in undergraduate contexts are more diverse and publicly oriented than those in school settings. Third, assessment approaches remain inconsistent and largely non-standardized across studies. This study contributes to the literature by conceptualizing science communication as a multidimensional and audience-oriented practice that evolves across educational levels. The findings suggest the need for more explicit integration of authentic communication tasks and the development of robust assessment frameworks, particularly in school science education.